Data utilized in African Green Climate Fund Agricultural Adaptation Projects and its availability in selected Decision Support Tools (DSTs) - Rosenstock, Todd S.; Joshi, Namita; Steward, Peter Richard; Kristal, Jones (2024)
The dataset aims to provide insight into the data needed for developing successful projects for the Green Climate Fund (GCF). It includes information on climate hazards, vulnerability, exposure, and response in 20 accepted agricultural adaptation projects in Africa.